Bacterial Adrenergic Sensors Regulate Virulence of Enteric Pathogens in the Gut - Cristiano G. Moreira (American Society for Microbiology, 2016)
ABSTRACT Enteric pathogens such as enterohemorrhagic Escherichia coli (EHEC) and Citrobacter rodentium, which is largely used as a surrogate EHEC model for murine infections, are exposed to several host neurotransmitters in the gut. An important chemical exchange within the gut involves the neurotransmitters epinephrine and/or norepinephrine, extensively reported to increase virulence gene expression in EHEC, acting through two bacterial adrenergic sensors: QseC and QseE. However, EHEC is unable to establish itself and cause its hallmark lesions, attaching and effacing (AE) lesions, on murine enterocytes. To address the role of these neurotransmitters during enteric infection, we employed C. rodentium. Both EHEC and C. rodentium harbor the locus of enterocyte effacement (LEE) that is necessary for AE lesion formation. Here we show that expression of the LEE, as well as that of other virulence genes in C. rodentium, is also activated by epinephrine and/or norepinephrine. Both QseC and QseE are required for LEE gene activation in C. rodentium, and the qseC and qseE mutants are attenuated for murine infection. C. rodentium has a decreased ability to colonize dopamine β-hydroxylase knockout (Dbh−/−) mice, which do not produce epinephrine and norepinephrine. Both adrenergic sensors are required for C. rodentium to sense these neurotransmitters and activate the LEE genes during infection. These data indicate that epinephrine and norepinephrine are sensed by bacterial adrenergic receptors during enteric infection to promote activation of their virulence repertoire. This is the first report of the role of these neurotransmitters during mammalian gastrointestinal (GI) infection by a noninvasive pathogen. IMPORTANCE The epinephrine and norepinephrine neurotransmitters play important roles in gut physiology and motility. Of note, epinephrine and norepinephrine play a central role in stress responses in mammals, and stress has profound effects on GI function. Bacterial enteric pathogens exploit these neurotransmitters as signals to coordinate the regulation of their virulence genes. The bacterial QseC and QseE adrenergic sensors are at the center of this regulatory cascade. C. rodentium is a noninvasive murine pathogen with a colonization mechanism similar to that of EHEC, enabling the investigation of host signals in mice. The presence of these neurotransmitters in the gut is necessary for C. rodentium to fully activate its virulence program, in a QseC/QseE-dependent manner, to successfully colonize its murine host. Our study data provide the first example of epinephrine and norepinephrine signaling within the gut to stimulate infection by a bacterial pathogen in a natural animal infection.